1996
DOI: 10.1016/0014-5793(96)00946-5
|View full text |Cite
|
Sign up to set email alerts
|

Reconstitution of proteasome activator PA28 from isolated subunits: optimal activity is associated with an α,β‐heteromultimer

Abstract: PA28, a 200 kDa activator of 20S proteasomes, was purified from human placenta and was gel electrophoretically resolved into two different subunits, a and [~. In reconstitution experiments, ¢z-subunits alone were found to re-associate forming homooligomers with an Mr of about 200 kDa, which elicit a stimulatory effect on proteasomal peptide-hydrolyzing activity, albeit at a moderate level. Under the same conditions, isolated ~-subunits were neither found to associate nor did they display stimulatory activity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
17
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 24 publications
3
17
0
Order By: Relevance
“…In the 11 S REG, ␣ and ␤ subunits are present in about equal amounts (36); thus these results are consistent with the idea that REG␤ subunits activate the proteasome. Alternatively, one could argue that REG␤ subunits function only to alter the conformation of the mutated REG␣ activation loop.…”
Section: Proteasome Activation Bysupporting
confidence: 80%
See 1 more Smart Citation
“…In the 11 S REG, ␣ and ␤ subunits are present in about equal amounts (36); thus these results are consistent with the idea that REG␤ subunits activate the proteasome. Alternatively, one could argue that REG␤ subunits function only to alter the conformation of the mutated REG␣ activation loop.…”
Section: Proteasome Activation Bysupporting
confidence: 80%
“…Thus, we call this region the activation loop. There are two reports that REG␤ is inactive (36,37), and it has recently been proposed that REG␤ functions only to modulate the activity of REG␣ (37). However, several publications from our laboratory have shown that REG␤, by itself, activates the proteasome (34,35,38).…”
mentioning
confidence: 99%
“…4 show REG␤ active at 42°C, other REG␤ preparations were markedly inactivated at 35°C. Accordingly, enzyme reactions incubated at 37°C may not detect REG␤ activity, and this is the reason that we assayed the recombinant REG homologs at room temperature rather than at 37°C as in previous studies (18,53). In conclusion, we are confident that REG␤ activates the proteasome, but its activity is more difficult to detect than that of REG␣ or REG␥.…”
Section: Discussionmentioning
confidence: 82%
“…The finding that REG␤ is a proteasome activator might be considered unexpected for two reasons. First, there are two reports that REG␤ does not activate the proteasome (2,53). Second, we have produced 31 monomeric mutants of REG␣ that cannot stimulate peptide hydrolysis by the proteasome.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a limited structural domain of one of the two subunits appeared to be required for binding of PA28 to the proteasome and resultant proteasome activation. Further support for a key role of the ␣ subunit in PA28 function was obtained in studies showing that the isolated ␣ subunit, prepared as a recombinant protein or electrophoretically separated from denatured native PA28, could activate the proteasome although not as efficiently as the native protein containing both ␣ and ␤ subunits (34,36,39,40). Thus, we hypothesized that the ␤ subunit might act to mediate function of the ␣ subunit, perhaps by increasing the affinity of PA28 for the proteasome.…”
mentioning
confidence: 99%